High Percentage of Methicillin-Resistant Staphylococcus aureus Isolates with Reduced Susceptibility to Glycopeptides in The Netherlands - Van Griethuysen, Arjanne (American Society for Microbiology, 2003)
While testing the in vitro activities of 14 antimicrobial agents against 107 methicillin-susceptible Staphylococcus aureus (MSSA) and 250 methicillin-resistant S. aureus (MRSA) isolates collected in The Netherlands, we found to our surprise that 19 (7.6%) MRSA isolates were suspected of having reduced susceptibilities to the glycopeptides when the Etest system (AB Biodisk, Solna, Sweden) was used with a large inoculum (no. 2 McFarland standard) and an extended incubation time (48 h) on brain heart infusion agar for MIC testing. Eventually, 15 of these isolates were classified as heterogeneously resistant to glycopeptides (heterogeneously glycopeptide-intermediate S. aureus [hGISA] isolates) according to the population analysis profile-area under the curve analysis. The MICs at which 50 and 90% of isolates are inhibited obtained with the Etest system with the large inoculum were as follows: for MSSA isolates, 3.0 and 4.0 μg/ml, respectively, for both teicoplanin and vancomycin; for MRSA isolates, 3.0 and 8.0 μg/ml, respectively, for teicoplanin, and 3.0 and 4.0 μg/ml, respectively, for vancomycin. This is the first report of hGISA isolates in The Netherlands.